Pendidikan Islam, Modernisasi Dan Kolonialisasi: Transformasi Lembaga Pendidikan Jam’iyatul Washliyah Tahun 1930-1942 - Sumantri, Solihah Titin; Deliana, Nia; Afif, Yusmicha Ulya (TADRIS: Jurnal Pendidikan Islam, 2021)
The work of al Washliyah organization in Sumatra between 1930 to 1942 responded to colonial-modernism in Indonesia in Islamic based education, which became the boundary between opposing and accepting the west modernisation. In the period of 1930-1942, Al Washliyah determined his education's content by considering several factors. First, because of society's situation and condition towards the demands of Islamic teachings as the spirit of fundamental teachings in fulfilling organizational education as contained in the statutes. Second, the existence of a revolutionary wave in education that was introduced by the colonial party, which then dissolved through local wisdom values ​​to create modern intellectual development. Third, The application of the Dutch educational subject matter contains many subjects that are never found in Islamic schools, such as in Pesantren, Surau, or others. This shows that material introduced by the Dutch contributes development in education so that there was a desire to equalize the progress achieved by the West. Fourth, the Islamic community's economic demands, the intellectuals from various social groups, required a worthy work facilities. Likewise, social equality in achieving education has triggered schools with available material without leaving religious content for schools of all Indonesians. Thus the demands for changes in the existing subject matter in Islamic schools are possible and are determined as educational content enforced in those three organization' schools.